Some Reflections on the Interface between Professional Machine Translation Literacy and Data Literacy - Ralph Krüger (Journal of Data Mining and Digital Humanities, 2023)
Due to the widespread use of data-driven neural machine translation, both by professional translators and layperson users, an adequate machine translation literacy on the part of the users of this technology is becoming more and more important. At the same time, the increasing datafication of both the private and the business sphere requires an adequate data literacy in modern society. The present article takes a closer look at machine translation literacy and data literacy and investigates the interface between the two concepts. This is done to lay the preliminary theoretical foundations for a didactic project aiming to develop didactic resources for teaching data literacy in its machine translation-specific form to students of BA programmes in translation/specialised communication.